Surgical outcomes of upper tract approach and lower tract approach in duplex kidney: Single center experience - Soratree Saingarm (2019)
© 2018, Faculty of Medicine Siriraj Hospital, Mahidol University. Objective: We reviewed the result of upper and lower tract approaches in duplex collecting systems at Siriraj Hospital between January 2011 and January 2017, focusing on reoperation rate and postoperative urinary tract infection. Methods: We analyzed the medical records of 57 patients with duplex kidneys, ectopic ureter and ureterocele. 45 patients were treated with open surgical therapy including upper tract approach which consisted of upper pole nephrectomy and ureteropyelostomy, and lower tract approach which was common sheath reimplantation. Information included age at operation, gender, ectopic ureter and ureterocele location, vesicoureteral reflux (VUR), hydrohephrosis status and presenting symptoms. Results: Upper tract approach was performed in 23 patients, 3 patients were reoperated because of persistent ureterocele in 2 cases and VUR in 1 case (13.6%, p = 0.233). One was lost to follow-up. Among 22 patients who underwent lower tract approach, no patient required second operation with antibiotic prophylaxis. Conclusion: In the absence of ureterocele and VUR, upper tract approach surgery appears to be successful treatment of duplex kidneys. When compared with upper tract approach, the lower tract approach surgery is more effective for open surgical therapy in duplex kidneys if sample size increases.